2019
DOI: 10.1111/jocn.14937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring women's health care experiences through an equity lens: Findings from a community clinic serving marginalised women

Abstract: Aims and objectives To explore how marginalised women perceive and rate equity‐oriented health care at a primary care clinic using items that evaluate patients' experiences of care. Background Despite an increased recognition of the importance of health care that is equity‐oriented, and that understands the patient within the context of the broader social determinants of health, inequities in health remain prevalent around the world. Design Items from the “EQUIP Primary Health Care" research programme were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The studies included in this review showed the range of people in a situation of social vulnerability assisted by Nursing. With regard to age, studies involving adults ( 16 - 17 , 19 , 21 , 23 - 25 ) , older adults ( 18 , 22 , 27 ) , children ( 15 ) and adolescents ( 20 ) stood out; regarding gender, there was predominance of studies involving women ( 16 - 17 , 21 , 23 - 24 ) ; and, regarding race/ethnicity, of studies associated with the Aboriginal ( 21 ) and African-American ( 26 ) population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included in this review showed the range of people in a situation of social vulnerability assisted by Nursing. With regard to age, studies involving adults ( 16 - 17 , 19 , 21 , 23 - 25 ) , older adults ( 18 , 22 , 27 ) , children ( 15 ) and adolescents ( 20 ) stood out; regarding gender, there was predominance of studies involving women ( 16 - 17 , 21 , 23 - 24 ) ; and, regarding race/ethnicity, of studies associated with the Aboriginal ( 21 ) and African-American ( 26 ) population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, they took into account the individual context, life history, experience, and family support. The assessment of needs fulfillment was carried out through home visits and hospitalizations, mainly through Sensitive Conditions to Primary Health Care (SCPHC) ( 15 , 18 - 19 , 21 - 23 , 25 , 27 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nessa perspectiva, os estudos descortinam a necessidade de que a categoria profissional deva lutar para assegurar acessibilidade à assistência qualificada, equitativa e humanizada às mulheres afetadas pelo aborto, independente de sua raça/cor, classe social ou faixa etária (20) . Em países onde essa assistência é assegurada e/ou o aborto é legalizado, outros aspectos da atenção às mulheres têm sido objeto de estudos, tais como: o direito de visualizar os produtos da concepção (30) , o acesso equitativo de mulheres marginalizadas (31) , e o aborto medicamentoso por meio da telemedicina (32) .…”
Section: Discussionunclassified